Satisfaction Of Retail Investors On The Structural Efficiency Of The Market: Evidence From A Developing Country Context - Rashid, Mamunur; Nishat, Md. Ainun (Asian Academy of Management (AAM), 2009)
Satisfied investors are a necessary element of the stock market. They help to finance rapid expansion in developing countries. This study explores the components of market structure that contribute to the satisfaction level of retail investors. Around 300 retail investors from 25 randomly selected brokerage houses registered with the Dhaka Stock Exchange, Bangladesh were surveyed using a structured questionnaire. Analyses reveal that most investors were young and inexperienced but educated, with shortages of skills and income. The investors put the strongest emphasis on effective investment analysis, followed by ease of the transaction process, effective information management and timely risk management. The trading experience of these investors was used as a moderating variable to investigate the impact of demographic variables and found to be insignificant. The study suggests the importance of effective regulation, disclosure requirements to ensure a supply of quality information, investor education and technology driven trading in brokerage houses for overall investor satisfaction